Polymer photovoltaics : materials, physics, and device engineering - Huang, Fei (Writer on polymer optoelectronics); Yip, Hin-Lap; Cao, Yong (Writer on optoelectronics) (RSC polymer chemistry series, 2015)
Polymer solar cells have gained much attention as they offer a potentially economic and viable way of commercially manufacturing lightweight, flexible and low-cost photovoltaics. With contributions from leading scientists, Polymer Photovoltaics provides an international perspective on the latest research for this rapidly expanding field. The book starts with an Introduction to polymer solar cells and covers several important topics that govern their photovoltaic properties including the chemistry and the design of new light harvesting and interfacial materials and their structure-property relationship; the physics for photocurrent generation in the polymer solar cells; new characterization tools to study morphology effect on the property of donor/acceptor bulk heterojunctions; new device concepts such as tandem cells and semi-transparent cells and advanced roll-to-roll processes for large-scale manufacturing of polymer solar cells. Written by active researchers, the book provides a comprehensive overview of the recent advancements in polymer solar cell technology for both researchers and students that are interested in this field.